Bảng tổng hợp tiếp thu, giải trình ý kiến góp ý về dự thảo Luật Giá (sửa đổi) xin ý kiến rộng rãi - Bộ Tài chính (2022)
Toàn văn Bảng tổng hợp tiếp thu, giải trình ý kiến góp ý về dự thảo Luật Giá (sửa đổi) xin ý kiến rộng rãi